Luther’s Trinitarian Hermeneutic and the Old Testament - Helmer, Christine 1965- (2002)
In this study, the author shows that Luther’s trinitarian understanding is shaped by the royal Psalms’ dialogical model as well as informed by a hermeneutics that moors a trinitarian semantics in the Hebrew text of the Old Testament. The analysis concentrates on Luther’s translation into German of two Hebrew names for God and of passages classically associated with the trinitarian doctrine (Psalm 110:1; Psalm 2:2.12). The result is a trinitarian structure of transparency. The text’s syntax, narrative and direct speech mirror literally the transparency of the divine essence through the distinguishing characteristics of each trinitarian person.